Multivariate Analysis of Metal Levels in Paddy Soil, Rice Plants, and Rice Grains: A Case Study from Shakargarh, Pakistan - Saadia R. Tariq; Nabila Rashid (Journal of Chemistry)
The present study aims at determining the relationship between trace metal levels in paddy soils, rice plants, and rice grains obtained from these plants. The levels of selected metals (Fe, Co, Ni, Cd, Pb, and Cr) were determined by atomic absorption spectrophotometry in the soil, rice plants, and rice grain samples collected from paddy fields. All the metals were present at enhanced levels in paddy soil. Among the selected metals, Fe, Ni, Cd, and Cr were predominantly associated with oxidizable fraction. The metals such as Cr, Ni, Co, and Fe were significantly positively correlated in soil and plants, but no such correlation was observed in soil-grain matrix evidencing that these metals have a soil-based origin in the plants, but they were not translocated to grains. The Pb content of soil was strongly positively correlated with plants as well as the grains. The principal component analysis and cluster analysis were used to depict the origin of enhanced metal levels in rice plants. Under the given field conditions, different metals possess different translocation behaviours from soil to roots to shoots to grains. There is a dire need to implement the strategies for wise and optimum use of agrochemicals.